Market penetration and business development strategies for Silver Atena’s Automated Test Equipments for the UK market - Das Gupta, Nilanjan (2010)
This dissertation revolves around the market penetration and business development strategies for Silver Atena’s (SA’s) Automated Test Equipment (ATE) in UK. The ATE has already been a successful product for Silver Atena Electronic Systems Engineering GmbH in Germany, by serving clients like EADS, MTU Aero Engines, Airbus, Audi, BMW etc. But the challenge presently lies while bringing their German culture and value to serve new target customers within the UK operations of Silver Atena (UK) Ltd. Along with extensive literature review on segmentation and the most opportunistic target segment for SA, this report has studies around cultural differences in Germany and UK not only from the customers’ perspective and but also from the organization’s standpoint. Through interviews in SA (UK) management and secondary research, an effort has been made to identify SA’s resources and capabilities which might be able to give them a sustainable competitive advantage in the future. Moreover an internal and external analysis of the aerospace business environment around the sale of ATE has been conducted to find the attractiveness of the marketplace and the organization’s strengths, weaknesses, opportunities and threats. Finally recommendations have been made for business development and market penetration strategies, based on the research analysis and findings.